The Case for Co-production in Singapore's Mental Healthcare - Lee, Ying Ying; Ang, Suying; Tang, Charmaine (Frontiers in Psychiatry, 2021)
For better or worse, there exists a power differential between psychiatrists and their patients in mental healthcare. Co-production was proposed to be the "third space" to offer truce between the professional-patient tension in mental healthcare. In Singapore, co-production is a new, but growing, approach to mental healthcare service delivery. In this commentary, we argue that co-production is not just a novel way to provide service, but a moral imperative. Recovery Colleges and its adoption in Singapore is discussed in some detail to highlight how co-production may be applied in practice.